THE INFLUENCE OF CRITICAL FACTORS ON THE BEHAVIOR INTENTION TO COMPUTERIZED ACCOUNTING SYSTEMS (CAS) IN CEMENT MANUFACTURES IN LIBYA - Abdullah Naheb, Omran; Sukoharsono, Eko Ganis; Baridwan, Zaki (Accounting Department,, 2017)
Due to the rapid change in technology, businesses prefer to track monetary transactions using computerized system and the advancements in information technology have eventually led to the introduction of Computerized Accounting Systems (CAS) to help produce relevant, trusted, and representative financial reports for both management and external users for decision-making without errors. The shifting from conventional accounting system in Libyan organizations to Computerized Accounting Systems (CAS) resulted in some company’s staff’s resistance on the adoption of the new technologies. Therefore, this study aims to examine the Influence of Critical Factors on the Behavior Intention to Computerized Accounting Systems (CAS) In Cement Manufactures In Libya which are, Performance Expectancy, Effort Expectancy, Facilitating Conditions, Self-efficacy and Task- technology fit (TTF) to accountant Behavioral Intentions (ABI) of using (CAS) in Libyans cements organizations. This study utilized quantitative research method and survey questionnaires distributed 240 forms to employee of in accounting and finance department in four biggest Libyan cement manufacturers, Al- Murgab, Lubda, Souk Al khamis and Zalitan. The 189 returned forms were analyzed using PLS software. The result of analysis hypothesis revealed that there is a significant effect among all variables to Behavioral Intentions, but, only, Effort Expectancy does not have impacts on the Behavior Intention to Computerized Accounting Systems (CAS) In Cement Manufactures In Libya.